2015
DOI: 10.1007/s11095-015-1677-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual Drug Delivery Using Lactic Acid Conjugated SLN for Effective Management of Neurocysticercosis

Abstract: The overall study paved the potential advances in brain targeting with synergistic acting drugs for effective management of NCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Nevertheless, the EE% of DAG in ILPs decreased by approximately 14% compared to the LPs, which was only about 44:3 ± 1:1% and may be due to the modification process. Similar results reported by Manjappa et al [37], Devi et al [38], and Peres-Filho et al [39] showed that the encapsulation efficiency of cargoes in liposomal formulations was reduced by 5%, 10%-12%, and 16%, respectively, after modification with anti-neuropilin-1, lactic acid, and folic acid, respectively. Furthermore, the determined loading molar ratio between EMO and DAG was 1 : 3.7 and 1: 2.7 in the prepared LPs and ILPs, respectively, which was consistent with the designed radiometric of EMO and DAG for synergistic effects (Figures S1 and S2).…”
Section: Resultssupporting
confidence: 84%
“…Nevertheless, the EE% of DAG in ILPs decreased by approximately 14% compared to the LPs, which was only about 44:3 ± 1:1% and may be due to the modification process. Similar results reported by Manjappa et al [37], Devi et al [38], and Peres-Filho et al [39] showed that the encapsulation efficiency of cargoes in liposomal formulations was reduced by 5%, 10%-12%, and 16%, respectively, after modification with anti-neuropilin-1, lactic acid, and folic acid, respectively. Furthermore, the determined loading molar ratio between EMO and DAG was 1 : 3.7 and 1: 2.7 in the prepared LPs and ILPs, respectively, which was consistent with the designed radiometric of EMO and DAG for synergistic effects (Figures S1 and S2).…”
Section: Resultssupporting
confidence: 84%
“…1 ml of SLN suspension free from unentrapped drug was placed in dialysis tube, which was suspended in a 200ml of PBS, pH 7.4 and placed on magnetic stirrer at the temperature of 37 ± 2 ° C with continuous stirring at moderate speed (dialysis membrane/ diffusion method). At specified time intervals i.e 0.5hr, 1 hr, 2 hr, 4hr, 6hr, 12hr and 24hr, the 5 ml of samples were collected and analysed by spectrophotometrically at λmax 269nm [16].…”
Section: In-vitro Drug Release Studiesmentioning
confidence: 99%
“…In recent years, SLNs open new perspectives in nanomedicines. There have been major efforts to develop SLNs systems that are able to improve the drug release profiles and increase the effectiveness of the formulations for the effective control of drug delivery systems [64][65][66]. Also, Muller et al have developed ideas about drug release of SLNs [67][68][69].…”
Section: Drug Releasementioning
confidence: 99%